The Placebo Effect: What's Interesting for Scholars of Religion? - Harrington, Anne (Zygon, 2011)
Abstract. The placebo effect these days is no longer merely the insubstantial, subjective response that some patients have to a sham treatment, like a sugar pill. It has been reconceived as a powerful mind-body phenomenon. Because of this, it has also emerged as a complex reference point in a number of high-stakes conversations about the metaphysical significance of experiences of religious healing, the possible health benefits of being religious, and the feasibility of using double-blind placebo-controlled trials to investigate the efficacy of prayer. In each of these conversations, the placebo effect is always pointing toward some larger issue, serving some larger agenda. The agendas, though, tend to pull in different directions, leading to a situation that feels at once fractured and stalemated. This essay reviews the main areas of interest, and proposes some specific issues where humanistic scholars of religion in particular might be able to introduce constructive and creative new perspectives.